A Proof-of-Concept Demonstration Using Musical Stimuli for The Measurement of Psychological Individual Differences - Galang, Adrianne John R.; Policarpio, Monica Renee G.; Xu, April Meryll; Nalipay, Ma. Jenina; Cabredo, Rafael (Philippine Social Sciences Review; Vol 74 No 2 (2022): PSSR Vol. 74 No. 2 2022, Ed. Jorge V. Tigno, 2025)
Given that there are well documented differences in terms of preferences for music, this study explored whether very basic melodic stimuli can be used as correlates of some psychological individual differences such as personality traits. We created a set of short musical stimuli which we manipulated in terms of basic melodic properties such as pitch range, key, and average pitch. In a university sample with a final count of 103 valid cases, we collected preference ratings, pupil dilation data, and questionnaire data on personality and demographic variables. We then used a machine learning technique to build decision trees that would provide insights on what patterns might be useful to pursue further in subsequent work. We found that there were suggestive patterns regarding how preferences for the set of musical stimuli related to self-reported personality traits. Despite very important limitations to the current results, we believe that there is potential for refining this technique to yield a potentially useful paradigm in the measurement of psychological individual differences.